2017
DOI: 10.3389/fnagi.2017.00059
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Integrity Declined Over 6-Months, but Dance Intervention Improved Integrity of the Fornix of Older Adults

Abstract: Degeneration of cerebral white matter (WM), or structural disconnection, is one of the major neural mechanisms driving age-related decline in cognitive functions, such as processing speed. Past cross-sectional studies have demonstrated beneficial effects of greater cardiorespiratory fitness, physical activity, cognitive training, social engagement, and nutrition on cognitive functioning and brain health in aging. Here, we collected diffusion magnetic resonance (MRI) imaging data from 174 older (age 60–79) adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
112
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(124 citation statements)
references
References 109 publications
(174 reference statements)
11
112
0
1
Order By: Relevance
“…Previous cross-sectional studies have shown that NAWM AD increases with advanced age (Hsu et al, 2010; Michielse et al, 2010) and can distinguish healthy older adults from those with mild cognitive impairment or dementia (Bosch et al, 2012). Longitudinal studies show that AD increases over relatively brief periods of time (i.e., <5 years) among older adults (Burzynska et al, 2017; Rieckmann et al, 2016; Sexton et al, 2014; Storsve et al, 2016), a finding that was confirmed in the current study. Previous studies that have examined the association between PA and WM integrity in older adults primarily have been cross-sectional and have suggested an inverse correlation between PA and WM diffusivity (Sexton et al, 2016).…”
Section: Discussionsupporting
confidence: 86%
“…Previous cross-sectional studies have shown that NAWM AD increases with advanced age (Hsu et al, 2010; Michielse et al, 2010) and can distinguish healthy older adults from those with mild cognitive impairment or dementia (Bosch et al, 2012). Longitudinal studies show that AD increases over relatively brief periods of time (i.e., <5 years) among older adults (Burzynska et al, 2017; Rieckmann et al, 2016; Sexton et al, 2014; Storsve et al, 2016), a finding that was confirmed in the current study. Previous studies that have examined the association between PA and WM integrity in older adults primarily have been cross-sectional and have suggested an inverse correlation between PA and WM diffusivity (Sexton et al, 2016).…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, although aerobic fitness is positively associated with cognitive abilities Colcombe and Kramer 2003), baseline aerobic fitness has rarely been investigated as a potential moderator of training-related change (cf. Burzynska et al 2017;Voss et al 2013). This is also paralleled by finding that fit older adults show less cognitive decline than their sedentary counterparts and that physical exercise can improve cognitive functions Colcombe and Kramer 2003).…”
Section: Determinants Of Cognitive Improvements Due To Training: Modesupporting
confidence: 49%
“…Future studies could examine the reverse order, which might yield different results given the evidence suggesting that aerobic exercises could boost subsequent cognitive performance (Chang et al 2012). Another future consideration would be to compare simultaneous multimodal training as done presently, against a more integrated multimodal intervention such as dance (Burzynska et al 2017), which has also shown positive effects on cognition and associated neuroanatomical changes in older adults.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…The Strengthening/Stretching/Stability group served as the active control condition. In a primary outcomes paper it was demonstrated that white matter (WM) integrity declined in all four conditions with the exception of WM in the fornix region which increased in the dance condition [33]. However, these changes in WM integrity were not associated with changes in processing speed.…”
Section: Methodsmentioning
confidence: 99%
“…Specific details of the trial and participant flow through the study have been previously published [33,34]. Briefly, all groups met at local campus recreation centers for approximately one hour three times per week for 24 weeks, and each session began with a warm-up consisting of light walking followed by stretching exercises targeting major muscle groups.…”
Section: Methodsmentioning
confidence: 99%